2006
DOI: 10.1016/j.jtcvs.2005.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and outcome in congenital ventricular diverticulum and aneurysm

Abstract: Congenital ventricular diverticulum and aneurysm are two distinct entities, with different histologic and morphologic characteristics and outcomes. Assessment of these differential characteristics is of importance for prenatal counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
157
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(160 citation statements)
references
References 11 publications
1
157
0
2
Order By: Relevance
“…Although the natural history of patients with idiopathic LVA/Ds is not completely understood, cases of sudden death resulting from ventricular arrhythmias or ventricular rupture have been reported (10). While the vast majority of ventricular arrhythmias arise from reentry circuits originating in idiopathic LVA/Ds (3), few reports have demonstrated an association between ventricular arrhythmia and idiopathic LVA/Ds in catheter-based electrophysiological studies due to the difficulty of performing detailed anatomical mapping of LVA/Ds.…”
Section: Discussionmentioning
confidence: 99%
“…Although the natural history of patients with idiopathic LVA/Ds is not completely understood, cases of sudden death resulting from ventricular arrhythmias or ventricular rupture have been reported (10). While the vast majority of ventricular arrhythmias arise from reentry circuits originating in idiopathic LVA/Ds (3), few reports have demonstrated an association between ventricular arrhythmia and idiopathic LVA/Ds in catheter-based electrophysiological studies due to the difficulty of performing detailed anatomical mapping of LVA/Ds.…”
Section: Discussionmentioning
confidence: 99%
“…Marijon et al demonstrated in their cohort of patients diagnosed with LVA/LVD a survival rate of only 30% after 4 years of follow-up. 30 That patient group, however, consisted of neonates or young children associated with other intra-and/or extracardiac malformations, which might represent a different risk group. 2,4 Reports of progressive enlargement or rupture of LVA/LVD exist exclusively in children; 8,31,32 the present series did not include patients below the age of 16 years, and this might explain, at least in part, the low cardiac mortality.…”
Section: Discussionmentioning
confidence: 99%
“…4) On the other hand, an aneurysm is generally a fibrous, saccular lesion with paradoxical contraction.…”
Section: Discussionmentioning
confidence: 99%